Facilitation of Tear Fluid Secretion by 3% Diquafosol Ophthalmic Solution in Normal Human Eyes - Yokoi, Norihiko; Kato, Hiroaki; Kinoshita, Shigeru (American journal of ophthalmology, 2014)
To evaluate the increase in tear fluid volume induced by 3% diquafosol ophthalmic solution in normal human eyes. Prospective, randomized, double-masked, comparative study. Twenty healthy adults (17 males and 3 females; mean age, 38.8 years) underwent topical instillation of 2 ophthalmic solutions, artificial tears in 1 eye and 3% diquafosol ophthalmic solution in the fellow eye, in a masked manner. The radius of curvature of the central lower tear meniscus was measured at 5, 10, 15, 30, and 60 minutes after instillation by use of reflective meniscometry, and subjects' self-evaluated symptoms of wetness and stinging using a visual analog scale. Changes after instillation in the radius of curvature from baseline (artificial tear group vs diquafosol group; mean ± standard error of the mean) were as follows: at 5 minutes, −0.008 ± 0.012 vs 0.045 ± 0.013; at 10 minutes, 0.001 ± 0.014 vs 0.057 ± 0.016; at 15 minutes, −0.012 ± 0.014 vs 0.037 ± 0.019; at 30 minutes, −0.010 ± 0.016 vs 0.030 ± 0.025; and at 60 minutes, −0.029 ± 0.012 vs −0.020 ± 0.012. The diquafosol group showed significantly greater values from 5 to 30 minutes after instillation. Of the 40 eyes, 13 showed abnormal tear film breakup time (≤5 seconds). The diquafosol group had significantly more wetness at 15 minutes after instillation than did the artificial tear group. Topical instillation of 3% diquafosol ophthalmic solution increases tear fluid on the ocular surface for up to 30 minutes in normal human eyes.